Upaya Meningkatkan Minat Belajar Teks Prosedur Melalui Pembelajaran Team Quiz Siswa Kelas VII MTs Islamiyah Petangguhan Galang - Rini Putriani Jamil; Susy Deliani; Arianto (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
The purpose of this study was to determine the results and interest in learning Procedure text through team quiz learning. The method used in this research is Classroom Action Research method. The samples in this study were 16 students of class VII of Mts Islamiyah Petangguhan Galang. Data to measure the level of student learning completeness is taken from test questions given directly to students. So it can be seen in the pre-cycle action before the implementation of the team quiz learning strategy, out of 16 students there were 4 students who obtained a complete score with a percentage of 25% obtained an average score of 55. While in cycle II the application of the team quiz learning strategy has increased again from 16 students there are 13 students who get a complete score with a percentage of 81.2% and get a score of 78.8. So it can be concluded that the results and students' interest in learning Indonesian language subjects with Procedural Text material have increased greatly with the use of Team Quiz learning strategies.